Synthesis and Characterization of new Schiff base Derived from Benzothiazole with (Salicyldehyde and Saccharin) and Complexes for some Metal Ions (Co, Ni, Cd and Hg) - Luay Ali Dhahi (Journal of Global Pharma Technology, 2018)
This research including preparation new derivatives for heterocyclic compounds are (1,3 benzothiazole), process synthesis in us research divided into two major pathways: First , synthesis 2- amino benzothiazole derivatives ethyl 2-aminobenzo[d]thiazole-6-carboxylate (HL).Second pathway ,reaction of salicyldehyde and saccharin with amine group of benzothiazole (HL) produced of Schiff's base compounds(HL1,HL2). The compound was characterized by FT-IR, UV-Vis and 1H, 13C-NMR spectra. The complexes of the bivalent ions (M+2 =Co, Ni, Cd and Hg) with Schiff bases derived to give ligands (HL1, HL2) were prepared and then reacted with metal salts in ethanol as a solvent in (1:2) ratio (M: L). the complexes which have the general formula [M (HLn) 2Cl2] when (n=1, 2). Have been prepared and characterized by FT-IR, UV-Vis spectra, conductivity measurements, magnetic susceptibility. The proposed geometrical structures for all complexes were octahedral.Keywords: ligand, Benzothiazole, Salicyldehyde, Saccharin, Schiff bases, Complexes.